Simulation and application of voltage SAG regulator - R., Daniel; Khan, Nasrullah; Mariun, Norman; Mahmood, Senan (2002)
Voltage SAG is one of dominant cause at power quality problems. The voltage sag problems impact to industrial process because control and protection equipment are sensitive to voltage sag. Electro-magnetic contactor is one of such a devices that is sensitive to voltage sag. Data shows that contactor, which is widely used for controlling motor, cannot work properly when there are 50% rms voltage reduction for a period longer than one cycle. This paper will describe a voltage sag regulator device that is especially use to minimize voltage sag impact at the contactor.